2017
DOI: 10.1161/circresaha.116.309048
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Abnormalities and Congenital Heart Disease

Abstract: In the past two decades it has become evident that individuals born with congenital heart disease (CHD) are at risk of developing life-long neurological deficits. Multifactorial risk factors contributing to neurodevelopmental abnormalities associated with CHD have been identified; however the underlying etiologies remain largely unknown and efforts to address this issue have only recently begun. There has been a dramatic shift in focus from newly acquired brain injuries associated with corrective and palliativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
108
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 174 publications
2
108
0
1
Order By: Relevance
“…Hospital mortality for neonates and infants with severe/complex congenital heart disease (CHD) has dramatically improved over the past 2 decades . However, many survivors of complex CHD repair are at significant risk for important neurodevelopmental morbidity . Within a wide range of brain regions, newly developed postoperative white matter (WM) injury is common .…”
Section: Introductionmentioning
confidence: 99%
“…Hospital mortality for neonates and infants with severe/complex congenital heart disease (CHD) has dramatically improved over the past 2 decades . However, many survivors of complex CHD repair are at significant risk for important neurodevelopmental morbidity . Within a wide range of brain regions, newly developed postoperative white matter (WM) injury is common .…”
Section: Introductionmentioning
confidence: 99%
“…Developmental heart and brain have complex interactions at multiple levels. For example, neural crest cells (NCCs), capable of differentiation into peripheral neurons and glia, migrate from the pharyngeal arch arteries (PAA) and heart outflow tract (OFT) to the primitive heart, and give rise to smooth muscle, connective tissue, and great arteries of the heart [4]. Notably, newborns with congenital heart defects exhibited a high frequency of neurodevelopmental deficits [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, neural crest cells (NCCs), capable of differentiation into peripheral neurons and glia, migrate from the pharyngeal arch arteries (PAA) and heart outflow tract (OFT) to the primitive heart, and give rise to smooth muscle, connective tissue, and great arteries of the heart [4]. Notably, newborns with congenital heart defects exhibited a high frequency of neurodevelopmental deficits [4,5]. Previous studies revealed that epigenetic regulatory mechanisms, such as DNA methylation [6], histone modifications [7], and chromatin remodeling [8][9][10][11], played essential roles in heart and neural development in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…It is now clear that the etiology of neurologic deficits in children with congenital heart disease (CHD) is cumulative and multifactorial. 7 Alterations in fetal cerebral oxygen delivery cause immature and delayed brain development before birth and before surgery. Lawrence and colleagues 8 recently demonstrated with a unique ''artificial womb'' system that prenatal and preoperative chronic hypoxemia result in similar alterations in microglial morphology in fetal sheep.…”
mentioning
confidence: 99%